Le neuroscienze, la psicoanalisi e la ricerca empirica nelle scienze umane - Fratini, Tommaso (Studi sulla Formazione/Open Journal of Education, 2011)
This paper considers the interface between psychoanalysis and neuroscience through the lens of mutual contributions and enrichment, with special attention to both the recent developments in psychoanalysis and the crisis of the society in which it works. Additionally, this paper takes up the problem of reductionism in the social sciences in relation to the risks of simplification theories that make ill use of the limitations of the scientific method.